PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) UNTUK MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK DI SEKOLAH DASAR - Laelatul Munawaroh; Rokmanah , Siti; Syachruroji , Ahmad (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2023)
This research aims to determine the role of using Information and Communication Technology (ICT)-based learning media to increase students' learning motivation in elementary schools. This research was carried out using a qualitative approach. The type of research used is qualitative descriptive research. The data collection method uses a research approach in the form of literature study. The research results obtained show that ICT-based learning media plays a very important role in 21st century learning. This can provide increased learning and student learning outcomes, showing interest, enthusiasm, focus, direction, in participating in learning activities. Apart from that, the use of ICT-based learning media can create an interesting and enjoyable learning atmosphere or what is called joyful learning. Apart from being a means of increasing students' learning motivation, ICT-based learning can also help teachers provide learning material more easily, familiarize teachers with adapting to rapidly developing times. Thus, it can be concluded that the use of Information and Communication Technology (ICT) can be used in learning and is suitable as a learning medium to increase students' learning motivation in elementary schools.